Halofuginone improves caustic-induced oxidative injury of esophagus in rats - YEGEN, BERRAK; ERCAN, FERİHA; KARADENİZ CERİT, KIVILCIM; YÜKSEL, MERAL (SPRINGER JAPAN KK, 2018)
The aim of this study is to evaluate the anti-inflammatory and anti-fibrotic effects of halofuginone in caustic esophageal burn injury in rats. Corrosive esophageal injury (CEI) was produced in male Wistar albino rats by instilling NaOH solution (1 ml, 37.5%) into the distal esophagus. Rats were decapitated on the 3rd day (early group) or 28th day (late group), and treated daily with either saline or halofuginone (100 A mu g/kg/day; i.p.), continued on alternate days after the third day. Histopathological evaluation and measurement of nitric oxide (NO), peroxynitrite (ONOO-) and oxygen-derived radicals by chemiluminescence (CL) were made in the distal 2 cm of the esophagus. Non-irrigated proximal esophageal samples were assessed for the levels of nuclear factor (NF)-kappa B, caspase-3, glutathione (GSH), malondialdehyde (MDA) and myeloperoxidase (MPO) activity. GSH, MDA, NF-kappa B and caspase-3 levels, and MPO activity in the proximal esophagus were not different among groups. Increased number of TUNEL (+) cells in the irrigated esophagus of the early and late caustic injury groups was reduced by halofuginone treatment. High microscopic damage scores in both early and late CEI groups were decreased with halofuginone treatment. NO, ONOO- and CL levels, which were elevated in the saline-treated early CEI group, were reduced by halofuginone treatment, but reduced NO and ONOO- levels in the late period of saline-treated group were increased by halofuginone. In addition to its anti-fibrotic effects, current findings demonstrate that halofuginone exerts antioxidant and anti-apoptotic actions and supports therapeutic potential for halofuginone in CEI-induced oxidative stress.
Keywords: Halofuginone; Caustic burn; Reactive oxygen metabolites; Oxidative injury; NITRIC-OXIDE; OXYGEN RADICALS; STRICTURES; INHIBITION; PREVENTION; INGESTION; CANCER; DAMAGE; CELLS; BURN